Insulin effects on honeybee appetitive behaviour - Mengoni Goñalons, Carolina (2016)
Worker honeybees (Apis mellifera) carry out multiple tasks throughout their adult lifespan. It has been suggested that the insulin/insulin-like signalling pathway participates in regulating behavioural maturation in eusocial insects. Insulin signalling increases as the honeybee worker transitions from nurse to food processor to forager. As behavioural shifts require differential usage of sensory modalities, our aim was to assess insulin effects on olfactory and gustatory responsiveness as well as on olfactory learning in preforaging honeybee workers of different ages. Adults were reared in the laboratory or in the hive. Immediately after being injected with insulin or vehicle (control), and focusing on the proboscis extension response, bees were tested for their spontaneous response to odours, sucrose responsiveness and ability to discriminate odours through olfactory conditioning. Bees injected with insulin have higher spontaneous odour responses. Sucrose responsiveness and odour discrimination are differentially affected by treatment according to age: whereas insulin increases gustatory responsiveness and diminishes learning abilities of younger workers, it has the opposite effect on older bees. In summary, insulin can improve chemosensory responsiveness in young workers, but also worsens their learning abilities to discriminate odours. The insulin signalling pathway is responsive in young workers, although they are not yet initiating outdoor activities. Our results show strong age-dependent effects of insulin on appetitive behaviour, which uncover differences in insulin signalling regulation throughout the honeybee workeŕs adulthood.